Peran Media dalam Agenda Setting: Diskursus Dampak Lingkungan Industri Kelapa Sawit Indonesia - Asma Nabila; Zulfi Prima Sani Nasution; Muhammad Akmal Agustira; Ratnawati Nurkhoiry (Jurnal Penelitian Kelapa Sawit, 2025)
Environmental management in Indonesia's palm oil industry has long been a topic of public discourse. While the industry contributes significantly to the national economy through economic growth, job creation, and rural development, it is often associated with environmental degradation. The media plays a critical role in shaping public perception and influencing policy agendas through issue framing. This study aims to analyze the differences in the framing of environmental issues related to the palm oil industry at various media levels (international, national, local, and NGO media). The study used a content analysis method on 470 news articles published between 2014-2023, using the Media Coverage Review approach and a categorization system based on issue themes and cause attribution. The results of the analysis show that there are significant differences in the causes and emphasis of issues between media types. International media and NGOs tend to associate the palm oil industry with deforestation, while national media highlight other sectors' contributions to environmental degradation. This discrepancy reflects an information gap that can influence the process of evidence-based policy formulation. These findings emphasize the importance of harmonizing media information to support fair and sustainable policy-making in the palm oil sector.